Analisis Kemampuan Pendinginan Water Cooling Tank (WCT) Berdasarkan Perubahan Daya Heater pada Untai FASSIP-6S - Rangga Aditya Faturahman; Roy Waluyo; Dwi Yuliaji; Putut Hery Setiawan; Shendy Akbar Maryadi; Muhammad Ahsan Fauzan; Mulya Juarsa (JTERA (Jurnal Teknologi Rekayasa), 2025)
Research on natural circulation phenomena is an important aspect in the development of passive safety systems in Nuclear Power Plants (NPP). To support this study, the National Research and Innovation Agency (BRIN) has designed and built a FASSIP-6S (Passive System Simulation Facility-6S) test facility, which serves to observe phenomena in passive cooling systems. The system is designed to operate without external power to extinguish reactors, dissipate decay heat, and resist the release of radioactive substances into the environment. This study is focused on testing the cooling ability of the Water-Cooling Tank (WCT) against variations in heating power. Experiments were carried out by varying the temperature of heating and cooling water, as well as measuring parameters such as power (W), inlet and outlet temperature (THin, THout, TCin, TCout), natural circulation flow (Q), and mass flow rate (m). The experiment was carried out on a medium-scale rectangular strand with dimensions of 2.5 meters high and 0.85 meters wide, with temperature measurements using a K-type thermocouple. The results show that the greater the heating power, the higher the cooling ability of the WCT. The average heat displacement at 1100W power is 793.03W, at 1300W it is 1026.51W, and at 1600W it is 1300.16W. The number of Reynolds obtained also increases as power increases, indicating an increase in natural circulatory flow